Investigating Methylation changes of Vimentin gene in Breast Cancer - Nahid Nejat; Seyed Ahmad Aleyasin; Seyed Abdolhamid Angaji; Saied Ayerian (Fasa University of Medical Sciences, 2018)
Background & Objective: Epigenetic changes are one of the most common changes in development of cancers. These changes alter the expression of certain genes that play important roles in the etiology of cancer. Increasing the expression of Vimentin gene due to epigenetic changes in Epithelial-Mesenchymal Transition(EMT) in breast carcinoma is well known. The relation between EMT and the malignancy invasion process has also been confirmed. Vimentin is the principal EMT marker that performs this task during metastasis. The purpose of this study is to investigate the methylation of the vitamin gene in a specific position. Material & methods: In this case-control study, the methylation pattern of the promoter of the Vimentin gene was evaluated in a specific site. Blood samples were taken from 30 breast cancer patients and 30 healthy individuals. DNA samples were digested with the methylation sensitive restriction enzyme. Control and treated DNA was amplified by PCR for qualitative investigation and real time PCR for quantitative analysis of methylation. Results: Using the Ct value and the%Me=100(e-0.7(ΔCt)) formula, the correlation between Vimentin hypomethylation and expression of Estrogen Receptor(ER), Progesterone Receptor(PR) and Human Epidermal growth factor Receptor2(HER2) status was checked (p-value <0.05). Conclusion: The results indicate that hypomethylated promoter of the Vim gene in the examined site correlates with ER, but does not have any correlation with PR and Her2, and hence the hypomethylation of the Vimentin gene in this position can be proposed as a molecular biomarker